Observation, Preconditioning and Recurrence of Exceptionally High Salinities in the Adriatic Sea - Mihanović, Hrvoje; Vilibić, Ivica; Šepić, Jadranka; Matić, Frano; Ljubešić, Zrinka; Mauri, Elena; Gerin, Riccardo; Notarstefano, Giulio; Poulain, Pierre-Marie (Frontiers in Marine Science, 2021)
The paper aims to describe the preconditioning and observations of exceptionally high salinity values that were observed in summer and autumn of 2017 in the Adriatic. The observations encompassed CTD measurements carried out along the well-surveyed climatological transect in the Middle Adriatic (the Palagruža Sill, 1961–2020), Argo profiling floats and several glider missions, accompanied with satellite altimetry and operational ocean numerical model (Mediterranean Forecasting System) products. Typically, subsurface salinity maximum, with values lower than 39.0, is observed in the Southern Adriatic (usually between 200 and 400 m), related to ingressions of saltier and warmer waters originating in the eastern Mediterranean (Levantine Intermediate Water—LIW). However, seasonally strong inflow of warm and high salinity waters (S > 38.8) has been observed much closer to the surface since spring 2015. The main LIW core deepened at the same time (to 400–700 m). Such double-maxima vertical pattern was eventually disturbed by winter convection at the beginning of 2017, increasing salinities throughout the water column. A new episode of very strong inflow of high salinity waters from the Northern Ionian was observed in late winter and spring of 2017, this time restricted almost to the surface. As most of 2017 was characterized by extremely dry conditions, low riverine inputs and warmer than usual summer over the Adriatic and Northern Ionian, salinity values above the sharp and shallow (15–40 m) thermocline significantly increased. The maximum recorded salinity was 39.26, as measured by the Argo float in the Southern Adriatic. Surface salinity maximum events, but with much lower intensity, have been documented in the past. Both past events and the 2017 event were characterized by (i) concurrence with overall high salinity conditions and cyclonic or transitional phase of the Adriatic-Ionian Bimodal Oscillating System, (ii) very low river discharges preconditioning the events for a year or more, (iii) higher-than-average heat fluxes during most of the summer and early autumn periods, forming a stable warm layer above the thermocline, and (iv) higher-than-average E-P (evaporation minus precipitation) acting on this warm surface layer. Importantly, the 2017 event was also preceded by strong near-surface inflow of very saline waters from the Northern Ionian in early 2017.